The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/v11010018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Indications and Compassionate Use of Phage Therapy: Personal Experience and Literature Review with a Focus on Osteoarticular Infections

Abstract: The history of phage therapy started with its first clinical application in 1919 and continues its development to this day. Phages continue to lack any market approval in Western medicine as a recognized drug, but are increasingly used as an experimental therapy for the compassionate treatment of patients experiencing antibiotic failure. The few formal experimental phage clinical trials that have been completed to date have produced inconclusive results on the efficacy of phage therapy, which contradicts the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
92
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 129 publications
(150 reference statements)
1
92
0
4
Order By: Relevance
“…Clinical improvement was observed in 92% of bacteriophages-treated patients. Bacteria were eliminated from the urine in 84% of patients (Perepanova et al 1995). Unfortunately, clinical trials conducted in Eastern Europe are poorly documented, and some reports are available in Russian or Georgian only (Chanishvili et al 2001).…”
Section: Characteristics Of Bacteriophagesmentioning
confidence: 99%
“…Clinical improvement was observed in 92% of bacteriophages-treated patients. Bacteria were eliminated from the urine in 84% of patients (Perepanova et al 1995). Unfortunately, clinical trials conducted in Eastern Europe are poorly documented, and some reports are available in Russian or Georgian only (Chanishvili et al 2001).…”
Section: Characteristics Of Bacteriophagesmentioning
confidence: 99%
“…However, after a century of use, there is increasing demand for rigorous evaluation of phage therapy, including in the most severe infections . There are case series with generally good outcomes, particularly in osteoarticular infections, diabetic foot infections, and chronic prostatitis . Two reviews detail the history of phage therapy in Russia and Eastern European countries and its application in specific human infections, a 2012 article provides a historical review of phage therapy over the years, and comprehensive up‐to‐date reviews are now also available …”
mentioning
confidence: 99%
“…Case studies of phage therapy continue to be added to the published literature (Table 1). Patey et al note that the generally positive results reported from isolated applications stand in contrast to the negative results of some clinical trials ( Table 2) (42). The routes of phage administration and dosing intervals, as well as the diversity of target bacteria and infection types, portend that the investigational use of phage therapy will likely continue for some time in the United States.…”
mentioning
confidence: 99%
“…Phages may be used as a complementary approach to currently available antimicrobial strategies rather than a replacement (42). As viruses, they and their components may be recognized by the immune system and eliminated via innate and/or adaptive defenses before reaching sites of infection, and their use may also compromise the future use of similar species in the same patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation